(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2017)
Following the presentation of a paper at the XV MAGIS — Gorizia International Spring School 2017, this article focuses on some of the theoretical premises that the legacy of postmodern thought offers for the understanding of contemporary forms of media resistance. In particular, it centres the attention on so-called ‘digital swarms’ that, also known as Distributed Denial-of-Service (DDoS), are one of the leading ‘weapons’ in the politics of digital media and network dissent. However, in the literature on hacktivism, these ‘swarming machines’ are predominantly de ned via an analogy with direct action, implying assumptions based on humanist epistemologies, which limits their politics as a matter of representation. With the objective of offering a possibility to move beyond the limits of such a metaphorical impasse, genealogy is suggested as a critical approach to link, through ideas of nonlinearity and difference, postmodern thinking and media archaeological investigations.